2022
DOI: 10.1093/icesjms/fsac057
|View full text |Cite
|
Sign up to set email alerts
|

Predicting density-dependent somatic growth in Norwegian spring-spawning herring

Abstract: Density-dependent growth, which might influence the effects of fisheries on a population, is often ignored when management strategies are evaluated, mainly due to a lack of appropriate models readily available to be implemented. To improve on this, we investigated if somatic growth in Norwegian spring-spawning herring (Clupea harengus) depends on cohort density using a formulation of the von Bertalanffy growth function on cohorts from 1921 to 2014 and found a significant negative correlation between estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This model provides dynamic description about the strength of density dependence with respect to environmental variations. In addition, our model embodies the density dependence of a combination of biological traits, including growth, fecundity and post‐recruitment mortality, which have been demonstrated separately by previous studies (Achord et al, 2003; Crozier et al, 2010; Raid et al, 2010; Stenevik et al, 2022; Wakiya et al, 2022). The density‐dependent effects presented by our mechanistic model were comparable to relevant field observations.…”
Section: Discussionmentioning
confidence: 95%
“…This model provides dynamic description about the strength of density dependence with respect to environmental variations. In addition, our model embodies the density dependence of a combination of biological traits, including growth, fecundity and post‐recruitment mortality, which have been demonstrated separately by previous studies (Achord et al, 2003; Crozier et al, 2010; Raid et al, 2010; Stenevik et al, 2022; Wakiya et al, 2022). The density‐dependent effects presented by our mechanistic model were comparable to relevant field observations.…”
Section: Discussionmentioning
confidence: 95%
“…The factors affecting fish somatic growth can arise from both environmental factors [31] and population dynamics through density dependence [32]. In Norwegian spring spawning herring, Stenevik et al [33] found a significant negative correlation between estimated asymptotic length and fish density. Investigating 70 fish populations from the northeast Atlantic, Zimmerman et al [34] found evidence for density dependence in both recruitment and growth.…”
Section: Discussionmentioning
confidence: 99%
“…For the long‐term investigation on NSS herring, the full recruitment (at age 2 years) time series covered the period from 1907 to 2017 (Stenevik et al., 2022). These data, however, did not include any estimation of uncertainty, in contrast with those from the ICES assessment outputs (1988–2021) (Table S1).…”
Section: Methodsmentioning
confidence: 99%